KONDISI SOSIAL EKONOMI MASYARAKAT DI SEKITAR AREAL PT. JAYA BUMI PASER DI KABUPATEN PASER PROVINSI KALIMANTAN TIMUR - Warman, Warman (FORUM EKONOMI, 2015)
Plans for utilization of timber in plantations covering 3,457 ha by  PT. Jaya Bumi Paser in Kutai regency of East Kalimantan province besides a positive impact also negatively impact the socio-economic and cultural conditions of the surrounding community. From the result of the research has been known that the average household income per capita per year is good enough or are not classified as poor. Besides As with farmers, civil servants and employees of the company, they also have side jobs such as working as a builder, selling groceries and fishing. Land area in controlled an average of  2.67 hectares per household obtained from parental inheritance, opening the forest itself, and some who do not own land, because they even have a family as head of the family, but they still ride in the elderly. The type and non-formal economic activity in general is quite varied, such as shops, kiosks groceries, cooperatives, coffee shops, and lodging. Economic infrastructure is sufficient. They use motorcycle for land transportation, or  motorboat for water transportation. The access to central city is easy to reach. Keyword: Social economic; cultural